Accuracy of PSA versus PCA3 in the Indication of Biopsy for the Diagnosis of Prostate Cancer - Almeida Vaz, Monique; da Silva Cordeiro Colenghi, Renato; Telles da Costa, Nathália; Gomes, Lucy; China Bezerra, Armando José; Bittencourt, Roberto José; Pereira, Rinaldo Wellerson (Revista de Medicina e Saúde de Brasília, 2019)
Prostate cancer is the most common neoplasm in men and the second largest cause of mortality due to neoplastic disease in this population. This study aims to analyze the biomarker that presents the highest accuracy for indication of prostate biopsy, between serum PSA and urine PCA3, aimed at the diagnosis of prostate cancer. It was performed a systematic review with the search for scientific studies in the PubMed, Bireme, Scielo, Cochrane Library, Health System Evidence, Epistemonikos databases and Capes thesis and dissertations from 2007 to 2017 using the descriptors "prostatic neoplasms", “prostate cancer”, “PCA3”, “DD3”, “prostate cancer antigen gene 3”, “PSA”, “prostate-specific antigen", "biopsy" and "diagnosis". The included studies were analyzed for risk of bias and applicability through the QUADAS-2 questionnaire. Nine articles were selected to compose this study. PCA3 was more accurate than PSA in predicting the biopsy result. The PCA3 sensitivity was between 53% and 94% and specificity between 36% and 86.7%, positive predictive value between 54% and 72% and negative predictive value over 60%. Eight of the nine articles included showed that the PCA3 accuracy decreases the indication of unnecessary prostate biopsies, presenting specificity higher than PSA. However, due to the risk of bias in the included studies, it was not possible to affirm that PCA3 is superior to PSA in the diagnosis of prostate cancer. Keywords: Prostate cancer. Biopsy. Diagnosis. Prostate-specific antigen. Prostate cancer Gene 3.